Understanding dietary and staple food transitions in China from multiple scales. - Xiao Chang; Ruth S DeFries; Liming Liu; Kyle Davis (PLoS ONE, 2018)
China is facing both non-communicable diseases (NCDs) and micronutrient deficiency, which have been largely related to transitions within Chinese diets, for example, the overconsumption of vegetable oils and animal-source products and decreasing consumption of coarse staple foods. In this study, we use three metrics-dietary diversity score (DDS), staple diversity score (SDS) and the proportion of coarse staple consumption (PoCS)- to investigate overall dietary transitions as well as trends in staple food consumption for nine provinces in China from 1997 to 2009. We also investigated how household characteristics, community urbanicity, and provincial conditions have affected household diets and the relationship between overall diet and staple diet across socio-economic gradients. Overall dietary diversity (DDS) showed consistent growth across all the provinces and subpopulations and was strongly associated with a household's socio-economic status. However, staple indicators (SDS and PoCS) showed notable difference both geographically and socio-economically. The relationship between overall dietary indicator (DDS) and staple indicators (SDS, PoCS) across SES gradients revealed that education is a more important influence than income in ensuring dietary balance and nutritional quality. Our findings show that programs aimed at promoting dietary balance and healthy staple diets must account for differences between provinces in terms of agronomic, nutritional, social, and economic conditions. By identifying the socio-economic characteristics and locations of the most nutritionally vulnerable populations, this study also points toward the need for policies that incorporate nutritional considerations into grain production systems and provide a strategy for enhancing China's national food security.